Teorema del umbral de Kermack y McKendrick para un modelo en tiempo discreto - Doig Camino, Elizabeth (Pontificia Universidad Católica del Perú, 2003)
The Theorem of Kermack and McKendrick is exposed for the continuous time, showing its analog later on for the pattern in discrete time, to which sorne preliminary concepts are defined on the pattern of the General Epidemic in continuous time and its relation with the pattern in discrete time.
Keywords: Epidemia Simple; Epidemia General En Tiempo Continuo y En Tiempo Discreto; Teorema del Umbral; Matemáticas; https://purl.org/pe-repo/ocde/ford#1.01.00